Pengaruh Green Accounting, Accountability, dan Natural Capital Terhadap Pembangunan Ekonomi - Wika Pebriana; Fenny Marietza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Economic development is an effort to improve the standard of living of a nation which is often measured by the high and low real income per capita. This study aims to analyze the interaction between the three variables and how these variables can affect economic development in plantation companies in Indonesia. Using a quantitative approach and secondary data from financial statements, through purposive sampling technique. Data analysis was carried out using panel data regression and processed using Eviews 13. The research population is Plantation Companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The research sample consisted of 32 companies. By using legitimacy theory as an analytical framework in the company's efforts to gain social recognition and meet stakeholder expectations. This study uses green accounting, accountability, and natural capital as independent variables, economic development as the dependent variable. The results showed that Green Accounting and Accountability have an effect on Economic Development, while natural capital has no effect on economic development.